Determinants of Public Investment Decision in Forex Robots Trading: Evidence from Indonesia - Uus Ahmad Husaeni,; Dwidja Priyatno,; Saptaning Ruju Paminto,; Hasbu Naim Syaddad, (Asian Journal of Business and Accounting, 2024)
Manuscript type: Research paper Research aims: This study aims to analyse the factors that influence investment decisions on forex trading robot users in Indonesia by using four factors that influence investment decisions: financial literacy, investment knowledge, financial behaviour, and risk tolerance. Design/Methodology/Approach: The method used in this research is quantitative with a survey approach. The data analysis technique used Structural Equation Modeling (SEM) through the Partial Least Square (PLS) approach. The data collection technique was carried out by distributing questionnaires with a Google form on the WA Forex robot trading user group. In the end, 200 users filled out the questionnaire. Research findings: This study shows that financial literacy and investment knowledge significantly influence public decisions. Meanwhile, financial behaviour and risk tolerance do not significantly affect people’s investment decisions in forex robot trading. This shows that forex trading robot users have good financial literacy and investment knowledge in deciding to invest. However, trading robot users have financial behaviour that tends to be wrong, so they are tempted to profit that is promised by 10-60 percent every month by forex trading robot companies without paying attention to the risk tolerance of the amount of property they invest. As a result, if the return from investment encounters obstacles, forex trading robot users will experience financial difficulties. Theoretical contribution/Originality: This study provides information that can help potential investors be careful and understand the risks when investing using forex trading robots. Research on investment decisions on forex trading robots in Indonesia is the first research that has been conducted due to the proliferation of companies offering forex trading robots that have led to Scams or Ponzi Schemes so that investors are harmed. Practitioner/Policy implication: The government of the Republic of Indonesia is to immediately pass the Law on the Use of Trading Robots in Indonesia so that it becomes the basis for the legality of trading using robots. Meanwhile, for the investment community using trading robots, even though trading robots promise large profits, they have weaknesses that allow the public to experience financial losses. Research limitations/Implications: Future research can consider the UTAUT model in measuring investment decisions in trading robots in Indonesia. Research regarding trading robots needs to be carried out continuously as public literacy material to avoid investment models that end in Ponzi schemes—also using a legal approach to be able to explain the criteria for trading robot providers that are close to or by the legislation in Indonesia which is currently being drafted.